On the Role of Human Capital and Instruments of Assistance for Rural Entrepreneurship and Development: Evidence from A Case Study Mountainous Italy - Nicola Meccheri; Gianluigi Pelloni (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2004)
Fostering entrepreneurship as a tool for the creation and support of rural businesses is a crucial goal for the integrated development and survival of rural economies. Despite the recognition of entrepreneurship as one of the main determinants of rural economic development, empirical research in this field is relatively sparse and the concept of rural entrepreneurship remains largely unexplored. Thus, there is little evidence on the role and function of rural entrepreneurs, the driving force behind the birth, survival and growth of rural enterprises. The present work, emerging from a larger project on rural entrepreneurship in the mountainous areas of southern Europe, aims to provide a contribution to filling this gap in knowledge. In this paper we present and analyse the results emerging from a questionnaire submitted to a sample of 123 entrepreneurs and rural businesses in a mountainous area of central Italy. The paper focuses on the correlation between entrepreneurial human capital and the adoption of instruments of assistance, and provides an assessment on their role in stimulating entrepreneurship in the specific area. In the light of the empirical results, we examine and propose potential policies for fostering entrepreneurship and the development of the rural region under study.
Keywords: 330; Ländliche Entwicklung; Wirtschaftspolitik; Humankapital; Entrepreneurship-Ansatz; Gebirge; Italien